Analisa Faktor Pengaruh Self-Regulated Learning Terkait Performance Goals terhadap Prestasi Akademik - Safira Firdaus; Lutfi Rachman; Marindra Firmansyah (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction: SRL (Self-Regulated Learning) is one of some factors influencing the college student’s academic achievement. By applying SRL well, academic performance will be improved, but, there are some difficulties to apply it such as setting the strategy of motivation. Some strategy of motivation formed by performance goals which includes good grade, employment prospect, and successful future. Hence, this study aims to observing the effect of performance goals forming the SRL and the effect of SRL formed by performance goals to academic achievement.Methods: This research used analytical descriptive observational design with explanatory squencial mixed method by collecting and analyzing data quantitatively with quitionairre and then qualitatively with focusec group disscusion. The sample is 175 college student of General Medicine in Malang Islamic University from the purpossive sampling counted by the amount of minimal criteria (Morgan and Kretjie Table), then analyzed the quality and relationship among the constructs by using PLS. After that, qualititative data was collected by the focused group disccusion with the 18 sample choosen by maximum variation (6 girls and 6 boys) and analyzed by content analysis.Result: In forming the SRL, performance goals show 0,985 for R square and >1,97 (P value 0)for T statistic so it prove the significant effect. While in affecting academic achievement, the SRL formed by performance goals shows non-significant effect because the the R square is 0,006 dan the T statistic is <1,97 (P value 0,255).Conclusion: The motivation of achieving good grades, employment prospect, and successful future (performance goals) are factors that form SRL, while the SRL formed by those performance goals does not affect the academic achievement. Keywords: Self-Regulated Learning, performance goal, academic achievement, student of general medicine